Past and future pesticide losses to Chinese waters under socioeconomic development and climate change. (1st September 2022) - Li, Ang; Wang, Mengru; Kroeze, Carolien; Ma, Lin; Strokal, Maryna
Abstract: Increasing pesticide use pollutes Chinese surface waters. Pesticides often enter waters through surface runoff from agricultural fields. This occurs especially during heavy rainfall events. Socio-economic development and climate change may accelerate future loss of pesticides to surface waters due to increasing food production and rainfall events. The main objective of this study is to model past and future pesticide losses to Chinese waters under socio-economic development and climate change. To this end, we developed a pesticide model with local information to quantify the potential pesticide runoff from near-stream agriculture to surface waters after heavy rainfall. We project future trends in potential pesticide runoff. For this, we developed three scenarios: Sustainability, "Middle of the Road" and Economy-first. These scenarios are based on combined Shared Socio-economic Pathways and Representative Concentration Pathways. We identified hotspots with high potential pesticide runoff. The results show that the potential pesticide runoff increased by 45% from 2000 to 2010, nationally. Over 50% of the national pesticide runoff in 2000 was in five provinces. Over 60% of the Chinese population lived in pesticide polluted hotspots in 2000. For the future, trends differ among scenarios and years. The largest increase is projected for the Economy-first scenario, where the potential pesticide runoff is projected to increase by 85% between 2010 and 2099. Future pesticide pollution hotspots are projected to concentrate in the south and south-east of China. This is the net-effect of high pesticide application, intensive crop production and high precipitation due to climate change. In our scenarios, 58%–84% of the population is projected to live in pesticide polluted hotspots from 2050 onwards. These projections can support the development of regional management strategies to control pesticide pollution in waters in the future. Highlights: We modeled future pesticide runoff from agriculture to surface waters in China. Over 50% of national pesticide runoff in 2000 was in five provinces. Pesticide runoff to surface water increased by 45% during 2000–2010, nationally. In the future, 58%-84% of Chinese population is projected to live in hotspots of pesticide pollution. In the Sustainability scenario, potential pesticide runoff will be at the level of 2010.